Trust-Based Probabilistic Broadcast Scheme for Mobile Ad Hoc Networks - Xu, Huaqiang; Si, Haipeng; Zhang, Hang; Zhang, Liren; Leng, Yan; Wang, Jingjing; Li, Dengwang (IEEE access, 2020)
The overhead caused by broadcast schemes cannot be neglected in mobile ad hoc networks. It is known that the probabilistic broadcast scheme is an effective approach to reduce overhead, in which nodes forward packets with a probability to reduce redundant retransmissions. In hostile environments, malicious nodes degrade network efficiency, and they should be prevented from route discovery and data transmission. In this case, routing packets forwarded by malicious nodes are redundant. This paper presents a Trust-based Probabilistic Broadcast scheme (TPB) focusing on reducing overhead, especially caused by malicious nodes, in which rebroadcast probability is determined based on nodes' trustworthiness. In order to obtain nodes' trust level, a light-weight trust management model is designed based on direct and recommended trust evidence. According to nodes' trust level, rebroadcast delay is calculated for rearranging the rebroadcast order of routing packets. Furthermore, a novel method based on nodes' trustworthiness is proposed to calculate rebroadcast probability, which prevents untrusted nodes from route discovery. The proposed trust-based probabilistic broadcast scheme is incorporated with existing routing protocol and its performance is evaluated by simulations. The numerical results show that the proposed scheme can secure network communication and reduce the routing overhead.